Impact of exchange rate volatility on trade: empirical evidence for the East Asian economies - Chee, Wooi Hooy; Baharumshah, Ahmad Zubaidi (University of Malaya, 2015)
We investigated the impact of real exchange rate (REX) volatility on the trade performance of six East Asian economies. Several break dates were detected in the REX series over the sample period of January 1990 to December 2008. Exchange rate volatility was determined to be inherently asymmetric in all of the currency markets. We found short-run exports to be adversely affected by REX volatility in four countries, although this response was small. For imports, REX volatility was found to have a negative effect in only two of the six countries (Singapore and Indonesia). In short, there was less evidence to support the hypothesis that currency volatility has a strong negative effect on trade flows in East Asian economies. We also addressed the possibility of endogeneity in regressors and allowed for heterogeneity across countries in the model parameters.